Hubungan Antara Motivasi Berprestasi Dengan Minat Wirausaha Pada Mahasiswa - WIDHIWARDANA, NOVANDO ANUGRAH; , Drs. Mohammad Amir, M.Si (2016)
RELATIONSHIP BETWEEN THE ACHIEVEMENT MOTIVATIONS WITH ENTREPRENEURIAL INTERESTS OF STUDENT NovandoAnugrah Mohammad Amir Psychology Facultiesof MuhammadiyahUniversity of Surakarta Basically, the economic growth a country is not in spite from the increasing number of residents that have spirit of entrepreneurship. But in Indonesia the people have less entrepreneurial soul, one reason i.e. students as a young generation has less interest toward entrepreneur. Aim of this research is to know the relation between achievement motivations with interest entrepreneurial so that the authors propose the hypothesis "there is a relationship between the achievement motivations with entrepreneurial interests." The subject in this study is the student of psychology Faculty, 2012 grade. Sampling technique was incidental sampling, i.e. anyone who by chance/incidental met with researchers can be used as a sample, if the person is seen incidentally found it suitable as a data source. Measuring instrument which is used to reveal research variables there are 2 kinds of measuring instrument, namely: (1) an achievement motivational scale, and (2) the scale of entrepreneurial interest. The data analysis in this study uses the product-moment correlation. Based on the analysis results so that obtained correlation between achievement motivation with entrepreneurial interest i.e. (r) of 0.653 with p = 0.000 where p < 0.01, this means there is a very significant positive relationship between achievement motivation with entrepreneurial interests. This means that the higher the achievementmotivation then higher entrepreneurial interest of students, instead the lower achievement motivation then the also lower entrepreneurial interest of students. The empirical mean of achievement motivation variable is a number of 113.70 and mean hypothetic a number of 97.5. So the empirical mean > hypotheticmean that illustrates that generally students have high achievementmotivation. Furthermore the mean empirical of entrepreneurial interest variable is a number of 99.23 and mean hypotheticis 82.5. So the empirical mean > hypothetic mean that means that in general students have also high entrepreneurial interest. The role of achievement motivation toward entrepreneurial interest or effective contribution (SE) is 42.6%. Keywords: achievement motivation, entrepreneurial interest, students.